Lack of phylogeographic structure in Nigerian village chickens revealed by mitochondrial DNA D-loop sequence analysis - Adebambo, Ayotunde Olufunmilayo; Mobegi, V.A.; Mwacharo, Joram M.; Oladejo, B.M.; Adewale, R.A.; Iiri, L.O.; Makanjuola, B.O.; Afolayan, O.; Bjornstad, G.; Han Jianlin; Hanotte, Olivier H. (2010)
Genetic diversity studies that utilize phenotypic and genetic information are informative when formulating breeding and conservation plans. The present study utilizes sequences of mitochondrial DNA (mtDNA) D-loop region of 232 village chickens from Southern and Northern Nigeria to determine the origin and diversity of Nigerian local chickens. Thirty-six polymorphic sites which generate 35 haplotypes are identified. Phylogenetic analyses group Nigerian local chickens to a single clade and 97.8% of the total maternal variation occurs within populations. Reference sequences representing the major chicken mtDNA lineages from Asia indicate the Indian subcontinent to be the likely main center of origin of Nigerian village chicken. Lack of phylogeographic structure among Nigerian village chickens suggest extensive genetic intermixing within the country. © Asian Network for Scientific Information, 2010.